Janus photo-thermal distillation membrane for marine oily sewage and preparation method of Janus photo-thermal distillation membrane
By modifying the adhesive layer on the PTFE film and spraying carbon nanotubes, combined with the construction of the polyvinyl alcohol-tanninic acid hydrogel layer, the problem of poor interface adhesion of traditional Janus film is solved, and the efficient anti-pollution and durability of Janus photothermal distillation membrane is achieved, which is suitable for treating complex ship oil-containing sewage.
Patent Information
- Application Number
- CN202510115085.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The poor interface adhesion of traditional Janus films leads to the fall of photothermal materials, reduces the durability and evaporation properties of the film, and makes it difficult to effectively deal with complex high-salt oil-containing wastewater.
The adhesive layer is modified on the hydrophobic PTFE base film and sprayed with photothermal material carbon nanotubes to form an intermediate layer to prevent the photothermal material from falling off. Subsequently, a polyvinyl alcohol-tannin hydrogel layer with rich hydroxyl groups is coated to form a uniform hydrophilic oleophobic layer, enhancing the anti-wetting and anti-pollution properties of the film.
It realizes the excellent robustness, wetting resistance, pollution resistance and durability of Janus photothermal distillation membrane, and is suitable for handling complex ship oil-containing wastewater.
Smart Images

Figure CN119819131A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil-water separation membrane materials, and in particular to a Janus photothermal distillation membrane for ship oily sewage and a preparation method thereof. Background Art
[0002] Oily wastewater from ships has always been an important source of marine pollution. Its easy diffusion, difficulty in degradation, and toxicity of oily mixtures have brought certain difficulties to the treatment and compliance of ship oily wastewater, which seriously threatens the ecological and environmental balance of the ocean and offshore areas, and is contrary to the current low-pollution, sustainable green marine ecological development model. Therefore, there is an urgent need for efficient and economical ship oily wastewater treatment technology. At present, common ship oily wastewater treatment methods include physical method, chemical method, physical and chemical method, and biological method. Among them, membrane separation technology has the advantages of simple operation, easy control, no need for external chemical reagents, environmental friendliness, and continuous operation. It is considered to be one of the most promising water treatment technologies in the 21st century.
[0003] Compared with the traditional pressure-driven membrane separation technology, photothermal membrane distillation (PMD) has been widely used in the field of oily and salty wastewater treatment due to its many advantages such as low operating pressure requirement (can operate under low pressure or even no pressure), high water quality, low energy consumption, wide application range, and high evaporation efficiency. Studies have found that its photothermal effect can reduce the viscosity of oil in high-concentration oily wastewater, increase the fluidity of oil to accelerate water evaporation, and greatly improve the separation efficiency of oil and water. In particular, the use of renewable energy solar energy can meet the sustainable development needs of green ocean construction, which is to save resources, meet environmental and ecological requirements, and obtain good economic benefits. Enhancing the anti-oil pollution ability of distillation membranes is another key and difficulty to ensure the efficient and stable treatment of ship oily wastewater by membrane distillation. Due to hydrophobic interactions, oil droplets can be quickly adsorbed on the surface of hydrophobic membranes, which leads to clogging and wetting of membrane pores, severely inhibiting water vapor transport, and ultimately reducing the durability of the membrane. Therefore, designing a photothermal anti-fouling distillation membrane is the key to expanding the application of membrane distillation in difficult ship oily wastewater.
[0004] Recent research results have shown that Janus oil-water separation membranes with different wettabilities can effectively treat complex high-salinity oily wastewater. The membrane combines a hydrophilic oleophobic top layer with a hydrophobic bottom layer with low surface energy and high roughness, showing effective repellency to surfactants and oily substances, thereby achieving excellent anti-oil and anti-wetting properties. However, the interface of conventional Janus membranes has poor adhesion, which may lead to the shedding of photothermal materials, thereby deteriorating the evaporation performance of long-term membrane distillation experiments. Therefore, photothermal Janus oil-water separation membranes with a strong layer structure are urgently needed to achieve the purpose of treating ship oily wastewater. Summary of the invention
[0005] The object of the present invention is to provide a Janus photothermal distillation membrane for ship oily wastewater and a preparation method thereof, so as to solve the above-mentioned technical problems.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a Janus photothermal distillation membrane for ship oily wastewater, the method comprising the following steps:
[0008] 1) mixing carbon nanotubes in an acidic solvent for acidification, filtering, drying and grinding to obtain acidified carbon nanotubes;
[0009] 2) mixing dopamine hydrochloride and polyethyleneimine in a buffer solution to obtain an adhesive solution and loading the adhesive solution on a PTFE membrane to obtain a modified PTFE membrane containing an adhesive layer;
[0010] 3) mixing the acidified carbon nanotubes in ethanol, and spraying the obtained acidified carbon nanotube mixed solution on the modified PTFE membrane containing the adhesive layer to obtain a CNT / PTFE membrane;
[0011] 4) polyvinyl alcohol and tannic acid are mixed in a mixed solvent, and the obtained polyvinyl alcohol-tannic acid mixed solution is sprayed on the CNT / PTFE membrane, and after gelation, a Janus photothermal distillation membrane for ship oily wastewater can be obtained.
[0012] Furthermore, the acidic solvent comprises sulfuric acid and nitric acid, and the volume ratio of the sulfuric acid to the nitric acid is 2 to 5:1.
[0013] Furthermore, the acidification treatment is carried out under heating, the heating temperature is 70 to 90° C., and the acidification treatment time is 2 to 4 hours.
[0014] Furthermore, the mass ratio of dopamine hydrochloride to polyethyleneimine is 1:1-1.5, the buffer is Tris-HCl buffer, and the concentration of polyethyleneimine in the buffer is 2-3 mg / L.
[0015] Furthermore, the adhesive liquid is loaded on the PTFE membrane for 10 to 14 hours, and the temperature of the adhesive liquid is 40 to 60°C.
[0016] Furthermore, the concentration of the acidified carbon nanotube mixed solution is 1 to 3 mg / mL, and the sprayed volume of the acidified carbon nanotube mixed solution is 1 to 3 mL.
[0017] Furthermore, in the step 4), the mixed solvent comprises ethanol and water in a volume ratio of 1:1 to 2, and the concentration of polyvinyl alcohol in the polyvinyl alcohol-tannic acid mixed solution is 20 to 30 mg / mL, and the concentration of tannic acid is 20 to 30 mg / mL.
[0018] Furthermore, the polyvinyl alcohol-tannic acid mixture is heated in a water bath before spraying, the water bath heating temperature is 80-100° C., and the water bath heating time is 5-7 hours; the spray volume of the polyvinyl alcohol-tannic acid mixture is 1-2 mL.
[0019] The present invention also provides a Janus photothermal distillation membrane for ship oily sewage.
[0020] Beneficial effects of the present invention:
[0021] The present invention modifies an adhesive layer on a hydrophobic PTFE-based membrane, and then sprays the photothermal material carbon nanotubes (CNT) thereon to firmly bond and form an intermediate layer, which gives the membrane excellent photothermal conversion performance and prevents the photothermal material from falling off; then a polyvinyl alcohol-tannic acid (PVA-TA) hydrogel coating rich in hydroxyl groups is coated to form a uniform hydrophilic and oleophobic layer, and finally a Janus photothermal distillation membrane with excellent firmness is obtained. In addition, a series of photothermal membrane distillation experiments were carried out, which proved that the Janus photothermal distillation membrane (HC1 / PTFE membrane) for ship oily wastewater of the present invention has excellent anti-wetting and anti-fouling properties, and is suitable for treating real ship oily wastewater with complex components in practical applications. The present invention proposes a feasible method for preparing a photothermal distillation membrane with both anti-wetting and anti-fouling properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Surface SEM images and cross-sectional SEM images of the Janus photothermal distillation membrane for ship oily wastewater obtained in Example 1 of the present invention, including surface SEM images of (a) PTFE, (b) HC1 / PTFE, (c) HC2 / PTFE and (d) HC3 / PTFE membranes; cross-sectional SEM images of (e) PTFE and (f) HC1 / PTFE membranes;
[0023] Figure 2 Surface AFM images of (a) PTFE and (b) HC1 / PTFE membranes;
[0024] Figure 3 (a) Air-water contact angles (WCAs) and underwater oil contact angles (UOCAs) of PTFE membrane and HC1 / PTFE membrane and (b) underwater oil dynamic contact process diagram of PTFE membrane and HC1 / PTFE membrane;
[0025] Figure 4(a) Surface temperature and infrared thermal imaging of HC1 / PTFE membrane under different light intensities and (b) UV-Vis-NIR absorption spectra of PTFE and HC1 / PTFE membrane;
[0026] Figure 5 (a) PTFE membrane and (b) HC1 / PTFE membrane at 1.0 kW·m -2 Permeate flux and salt rejection curves after gradual introduction of SDS using 3.5wt% NaCl as feed under sunlight intensity and no light conditions;
[0027] Figure 6 (a) PTFE membrane and (b) HC1 / PTFE membrane at 1 kW·m -2 Permeation flux and salt rejection curves of 3.5wt% NaCl with oily material (1000ppm n-hexadecane) as feed under sunlight intensity and no light conditions;
[0028] Figure 7 (a) PTFE membrane and (b) HC1 / PTFE membrane at 1 kW·m -2 Permeation flux and salt rejection curves of actual seawater with added surfactant and oily substances (0.4 mMSDS and 1000 ppm n-hexadecane) under sunlight intensity and no light conditions. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing a Janus photothermal distillation membrane for ship oily wastewater, the method comprising the following steps:
[0030] 1) mixing carbon nanotubes in an acidic solvent for acidification, filtering, drying and grinding to obtain acidified carbon nanotubes;
[0031] 2) mixing dopamine hydrochloride and polyethyleneimine in a buffer solution to obtain an adhesive solution and loading the adhesive solution on a PTFE membrane to obtain a modified PTFE membrane containing an adhesive layer;
[0032] 3) mixing the acidified carbon nanotubes in ethanol, and spraying the obtained acidified carbon nanotube mixed solution on the modified PTFE membrane containing the adhesive layer to obtain a CNT / PTFE membrane;
[0033] 4) polyvinyl alcohol and tannic acid are mixed in a mixed solvent, and the obtained polyvinyl alcohol-tannic acid mixed solution is sprayed on the CNT / PTFE membrane, and after gelation, a Janus photothermal distillation membrane for ship oily wastewater can be obtained.
[0034] In the present invention, the acidic solvent comprises sulfuric acid and nitric acid, and the volume ratio of the sulfuric acid to the nitric acid is 2 to 5:1, preferably 3 to 4:1, and more preferably 3:1.
[0035] In the present invention, the acidification treatment is carried out under heating, the heating temperature is 70-90°C, preferably 75-85°C, and more preferably 80°C; the acidification treatment time is 2-4h, preferably 3h.
[0036] In the present invention, the mass ratio of dopamine hydrochloride to polyethyleneimine is 1:1-1.5, preferably 1:1; the buffer is Tris-HCl buffer, and the concentration of polyethyleneimine in the buffer is 2-3 mg / L, preferably 2 mg / L.
[0037] In the present invention, the adhesive liquid is loaded on the PTFE membrane for 10 to 14 hours, preferably 12 hours; the temperature of the adhesive liquid is 40 to 60°C, preferably 45 to 55°C, and more preferably 50°C.
[0038] In the present invention, the concentration of the acidified carbon nanotube mixed solution is 1-3 mg / mL, preferably 2 mg / mL; the spraying volume of the acidified carbon nanotube mixed solution is 1-3 mL, preferably 2 mL.
[0039] In the present invention, in the step 4), the mixed solvent comprises ethanol and water in a volume ratio of 1:1 to 2, and the volume ratio is preferably 1:1; the concentration of polyvinyl alcohol in the polyvinyl alcohol-tannic acid mixed solution is 20 to 30 mg / mL, preferably 22 to 29 mg / mL, and more preferably 25 to 28.5 mg / mL; the concentration of tannic acid is 20 to 30 mg / mL, preferably 22 to 29 mg / mL, and more preferably 25 to 28.5 mg / mL.
[0040] In the present invention, the polyvinyl alcohol-tannic acid mixture is heated in a water bath before spraying, and the water bath heating temperature is 80-100°C, preferably 85-95°C, and more preferably 90°C; the water bath heating time is 5-7h, preferably 6h; the volume of the polyvinyl alcohol-tannic acid mixture sprayed is 1-2mL, preferably 1mL.
[0041] The present invention also provides a Janus photothermal distillation membrane for ship oily sewage.
[0042] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0043] Example 1
[0044] 1) Dissolve 2 g of carbon nanotubes in a mixed solvent (80 mL, H2SO4 / HNO3=3:1, v / v) at 80°C for 3 h, then dilute the mixed solution to 2 L, let it settle and remove the supernatant. Then vacuum filter, freeze-dry and grind to obtain acidified carbon nanotube powder.
[0045] 2) Dopamine hydrochloride (2 mg / L) and polyethyleneimine (2 mg / L) were dissolved in Tris-HCl buffer, stirred at 500 rpm for 5 min, and then a polytetrafluoroethylene membrane was placed on the above solution at 50°C for 12 h. The PDA / PEI-modified PTFE membrane was named P-PTFE.
[0046] 3) The acidified carbon nanotubes were dissolved in anhydrous ethanol to obtain a 2 mg / mL acidified carbon nanotube mixed solution, which was then treated with an ultrasonic pulverizer for 30 min. Different volumes (1 mL, 2 mL, and 3 mL) of the acidified carbon nanotube mixed solution were sucked into a spray gun. It was then evenly sprayed on the P-PTFE to obtain a CNT / PTFE membrane, referred to as C n / PTFE (n is the volume of the acidified carbon nanotube mixture).
[0047] 4) Dissolve 3g of polyvinyl alcohol and 3g of tannic acid in a mixed solvent (105mL, ethanol / deionized water = 1:1, v / v). Then heat in a 90℃ water bath for 6h, and then add 1mL of the polyvinyl alcohol-tannic acid mixture to the spray gun. Then, spray these liquids evenly on the C n / PTFE surface. After the solvent evaporates, the hydrogel coating is obtained and named HC n / PTFE (n represents the volume of CNTs). The final ship oily wastewater was stored in deionized water using a Janus photothermal distillation membrane for subsequent testing.
[0048] Test Case
[0049] The HC1 / PTFE, HC2 / PTFE and HC3 / PTFE membranes obtained in Example 1 were characterized and their performance tested.
[0050] Test method: The surface morphology of the membrane was observed using a field emission scanning electron microscope (FESEM, FEI, quanta250FEG). The light absorbance of the membrane was measured using an ultraviolet-visible-near infrared (UV-vis-NIR) spectrophotometer system (UH4150, Hitachi). The surface roughness of the membrane was characterized by an atomic force microscope (AFM, JPK, NanoWizard4). The water contact angle (WCA) and underwater oil contact angle (UOCA) in air were measured using an optical goniometer (HARKE-SPCAX1S, China) to characterize the wettability of the membrane. The infrared thermal imager (Infra-Tec, ) monitor the surface temperature change of the membrane. 1.0kW·m -2 The light intensity corresponds to 1 sun. The mass and conductivity are measured by electronic balance and conductivity meter respectively.
[0051] (1) Surface morphology:
[0052] like[ Figure 1 (a)] As shown, the original hydrophobic PTFE membrane exhibits a rough and porous morphology with a unique fiber nodule network arrangement structure. Figure 1 (bd)] The smooth hydrogel layer and the CNT photothermal intermediate layer embedded under the hydrogel layer can be seen. Figure 1 (ef)] The cross-sectional comparison diagram also shows that the Janus photothermal distillation membrane has a clearly layered structure.
[0053] (2) AFM test:
[0054] from[ Figure 2 (a)] and [ Figure 2 (b)] It can be seen that the Rq value of the original substrate is 223nm, while the Rq value of the HC1 / PTFE membrane is 27.3nm. The significant decrease in the Rq value shows that the surface roughness of the membrane is greatly reduced, which further provides additional evidence for the successful construction of the smooth hydrogel layer.
[0055] (3) Contact angle test:
[0056] [ Figure 3 (a)] The wettability and oleophobicity of the PTFE membrane and HC1 / PTFE membrane are intuitively illustrated by water contact angle (WCA) and underwater oil contact angle measurements. The high WCA (>126°) on both sides of the PTFE accompanied by low UOCA (<22°) indicates that the original substrate is inherently hydrophobic and oleophilic, which may lead to poor permeation flux and inability to resist oil. In contrast, the front side of the HC1 / PTFE membrane exhibits excellent oleophobicity with a UOCA of 138.3°, which is due to the highly hydrated nature of the hydrogel layer, endowing the modified membrane with oil resistance. As shown in [ Figure 3 (b)] As shown, the oil droplets do not adhere to the modified membrane at all, demonstrating its excellent anti-oil pollution performance.
[0057] (4) Photothermal performance test:
[0058] The surface temperature of HC1 / PTFE membrane was monitored under different light intensity conditions by infrared thermal imaging during the PMD experiment. Figure 4 (a)] It can be seen that when the solar radiation intensity changes from 0kW·m -2 Increased to 1.5kW·m -2When the temperature of the HC1 / PTFE membrane rises rapidly from 48.1° C. to 52.7° C., it can be seen that the HC1 / PTFE membrane of the present invention has excellent photothermal performance and can be applied to the evaporation of high-salinity oily wastewater.
[0059] In order to further confirm the excellent photothermal conversion performance of HC1 / PTFE membrane, its light absorption performance was characterized by UV-Vis-NIR spectroscopy. Figure 4 (b)] shows that in the wavelength range of 200-2500nm, the PTFE membrane has significantly lower light absorption in the entire spectral region. In contrast, the average light absorption of the HC1 / PTFE membrane is 91.5%, which is 4.7 times that of the PTFE membrane, which is beneficial for subsequent photothermal conversion and solar steam generation. These results show that carbon nanotubes can expand the propagation path of light and thus obtain better light absorption.
[0060] (5) Anti-wetting performance test:
[0061] A mixture of a representative surfactant (SDS) and 3.5 wt% NaCl solution was used as feed to evaluate the anti-wetting properties of HC1 / PTFE membranes and control PTFE membranes. Starting from the 60th minute, SDS was added every 2 hours to gradually increase the SDS concentration in the feed solution to 0.4 mM. Figure 5 (ab)] As shown in Figure 5, each membrane exhibited relatively stable permeation flux and ideal salt rejection (>99.9%) within the first hour when the feed did not contain SDS. However, the salt rejection of the PTFE membrane decreased significantly after 0.4 mMSDS was added. In contrast, the modified membrane still exhibited excellent permeation flux and salt rejection even under the conditions of 0.4 mMSDS-containing feed and 7 h PMD experimental time [ Figure 5 (b)]. These results confirm that the Janus photothermal distillation membrane for ship oily wastewater prepared in the present invention has excellent anti-wetting properties.
[0062] (6) Antifouling performance test:
[0063] A saline solution containing 1000 ppm n-hexadecane was used as the feed solution to evaluate the antifouling property of the membrane. The permeation flux of the PTFE membrane dropped sharply after the start of the PMD test. Figure 6 (a)], which means that the control PTFE membrane was seriously fouled by oily substances, which led to a significant decrease in water flux. In contrast, the HC1 / PTFE membrane showed stable permeation flux and excellent salt rejection throughout the test [ Figure 6 (b)]. These results confirm that the HC1 / PTFE membrane has excellent anti-oil pollution ability.
[0064] (7) Film durability test:
[0065] The actual durability of the HC1 / PTFE membrane in treating complex oily saline wastewater was verified by treating simulated ship oily wastewater (real seawater, 0.4 mMSDS, 1000 ppm n-hexadecane) in a 10-hour PMD experiment. Soon after the start of the PMD experiment, it was observed that the salt rejection rate of the PTFE membrane dropped rapidly [ Figure 7 (a)]. In addition, the sudden increase in permeate flux also indicates that the PTFE membrane is wetted, allowing the feed solution to pass through the membrane pores. In contrast, the HC1 / PTFE membrane maintained a stable permeate flux and excellent salt rejection (>99.9%) throughout the 10-hour experiment, reflecting its excellent practical durability. Figure 7 (b)]. These results indicate that the Janus photothermal distillation membrane prepared in the present invention exhibits good application prospects in treating real high-salinity wastewater with complex components.
[0066] Example 2
[0067] 1) 2 g of carbon nanotubes were dissolved in a mixed solvent (100 mL, H2SO4 / HNO3=4:1, v / v) at 80°C for 3 h, and then the mixed solution was diluted to 2 L, allowed to settle and the supernatant was removed. The mixture was then vacuum filtered, freeze-dried and ground to obtain acidified carbon nanotube powder.
[0068] 2) Dopamine hydrochloride (2 mg / L) and polyethyleneimine (3 mg / L) were dissolved in Tris-HCl buffer, stirred at 500 rpm for 5 min, and then a polytetrafluoroethylene membrane was placed on the above solution at 50°C for 12 h. The PDA / PEI-modified PTFE membrane was named P-PTFE.
[0069] 3) The acidified carbon nanotubes were dissolved in anhydrous ethanol to obtain a 2 mg / mL acidified carbon nanotube mixed solution, which was then treated with an ultrasonic pulverizer for 30 min. 1 mL of the acidified carbon nanotube mixed solution was sucked into a spray gun, which was then evenly sprayed on the P-PTFE to obtain a CNT / PTFE membrane.
[0070] 4) Dissolve 3g of polyvinyl alcohol and 3g of tannic acid in a mixed solvent (105mL, ethanol / deionized water = 1:1, v / v). Then heat in a 90℃ water bath for 6h, and add 1mL of the above polyvinyl alcohol-tannic acid mixture to the spray gun. Then, spray these liquids evenly on the surface of CNT / PTFE. After the solvent evaporates, a hydrogel coating is obtained, named HCNT / PTFE. Finally, the ship's oily wastewater is stored in deionized water using a Janus photothermal distillation membrane for later testing.
[0071] Example 3
[0072] The water bath temperature in step 4) of Example 1 was changed to 100° C., the water bath time was changed to 5 h, the spray volume of the polyvinyl alcohol-tannic acid mixture was changed to 2 mL, and the other conditions were the same as in Example 1.
[0073] Example 4
[0074] The amount of polyvinyl alcohol in step 4) of Example 1 was changed to 2.5 g, and the amount of tannic acid was changed to 2.2 g. Other conditions were the same as in Example 1.
[0075] Example 5
[0076] 1) Dissolve 2 g of carbon nanotubes in a mixed solvent (100 mL, H2SO4 / HNO3=3:1, v / v) at 70°C for 4 h, then dilute the mixed solution to 2 L, let it settle and remove the supernatant. Then vacuum filter, freeze-dry and grind to obtain acidified carbon nanotube powder.
[0077] 2) Dopamine hydrochloride (2 mg / L) and polyethyleneimine (3 mg / L) were dissolved in Tris-HCl buffer, stirred at 500 rpm for 5 min, and then a polytetrafluoroethylene membrane was placed on the above solution at 50°C for 12 h. The PDA / PEI-modified PTFE membrane was named P-PTFE.
[0078] 3) The acidified carbon nanotubes were dissolved in anhydrous ethanol to obtain a 1 mg / mL acidified carbon nanotube mixed solution, which was then treated with an ultrasonic pulverizer for 30 min. 2 mL of the acidified carbon nanotube mixed solution was sucked into a spray gun, which was then evenly sprayed on the P-PTFE to obtain a CNT / PTFE membrane.
[0079] 4) Dissolve 3g of polyvinyl alcohol and 3g of tannic acid in a mixed solvent (105mL, ethanol / deionized water = 1:1, v / v). Then heat in a 90℃ water bath for 6h, and add 1mL of the above polyvinyl alcohol-tannic acid mixture to the spray gun. Then, spray these liquids evenly on the surface of CNT / PTFE. After the solvent evaporates, a hydrogel coating is obtained, named HCNT / PTFE. Finally, the ship's oily wastewater is stored in deionized water using a Janus photothermal distillation membrane for later testing.
[0080] Example 6
[0081] The concentration of the acidified carbon nanotube mixed solution in Example 5 was changed to 3 mg / mL, the spraying volume of the acidified carbon nanotube mixed solution was changed to 1 mL, and the other conditions were the same as in Example 1.
[0082] The Janus photothermal distillation membrane prepared in Example 6 was subjected to a PMD experiment for 12 hours to treat simulated ship oily wastewater (containing 35 g / L sodium chloride and 1200 ppm lubricating oil). During the entire operation, the photothermal membrane exhibited excellent resistance to oil pollution and stable permeation flux, and the salt rejection rate was always greater than 99.9%.
[0083] As can be seen from the above embodiments, the present invention provides a Janus photothermal distillation membrane for ship oily sewage and a preparation method thereof. The present invention modifies an adhesive layer on a PTFE membrane substrate, and then sprays the photothermal material carbon nanotubes onto the adhesive layer to obtain a CNT / PTFE membrane, which effectively promotes photothermal conversion and prevents the photothermal material from falling off; then, polyvinyl alcohol-tannic acid (PVA-TA) with rich hydroxyl groups is in situ gelled on the CNT / PTFE membrane to form a uniform hydrophilic and oleophobic hydrogel layer, which will integrate and strengthen the "pollution resistance" mechanism on the membrane surface, and the photothermal Janus distillation membrane finally obtained has excellent durability, anti-wetting, anti-pollution and anti-pollution durability.
[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a Janus photothermal distillation membrane for ship oily wastewater, characterized in that: The method comprises the following steps: 1) mixing carbon nanotubes in an acidic solvent for acidification, filtering, drying and grinding to obtain acidified carbon nanotubes; 2) mixing dopamine hydrochloride and polyethyleneimine in a buffer solution to obtain an adhesive solution and loading the adhesive solution on a PTFE membrane to obtain a modified PTFE membrane containing an adhesive layer; 3) mixing the acidified carbon nanotubes in ethanol, and spraying the obtained acidified carbon nanotube mixed solution on the modified PTFE membrane containing the adhesive layer to obtain a CNT / PTFE membrane; 4) polyvinyl alcohol and tannic acid are mixed in a mixed solvent, and the obtained polyvinyl alcohol-tannic acid mixed solution is sprayed on the CNT / PTFE membrane, and after gelation, a Janus photothermal distillation membrane for ship oily wastewater can be obtained.
2. The method for preparing a Janus photothermal distillation membrane for ship oily wastewater according to claim 1, characterized in that: The acidic solvent comprises sulfuric acid and nitric acid, and the volume ratio of the sulfuric acid to the nitric acid is 2 to 5:
1.
3. The method for preparing a Janus photothermal distillation membrane for ship oily wastewater according to claim 1 or 2, characterized in that: The acidification treatment is carried out under heating, the heating temperature is 70-90° C., and the acidification treatment time is 2-4 hours.
4. The method for preparing a Janus photothermal distillation membrane for ship oily wastewater according to claim 3, characterized in that: The mass ratio of dopamine hydrochloride to polyethyleneimine is 1:1-1.5, the buffer is Tris-HCl buffer, and the concentration of polyethyleneimine in the buffer is 2-3 mg / L.
5. The method for preparing a Janus photothermal distillation membrane for ship oily wastewater according to claim 1, 2 or 4, characterized in that: The adhesive liquid is loaded on the PTFE membrane for 10 to 14 hours, and the temperature of the adhesive liquid is 40 to 60°C.
6. The method for preparing a Janus photothermal distillation membrane for ship oily wastewater according to claim 5, characterized in that: The concentration of the acidified carbon nanotube mixed solution is 1-3 mg / mL, and the sprayed volume of the acidified carbon nanotube mixed solution is 1-3 mL.
7. The method for preparing a Janus photothermal distillation membrane for ship oily wastewater according to claim 1 or 6, characterized in that: In the step 4), the mixed solvent comprises ethanol and water in a volume ratio of 1:1-2, and the concentration of polyvinyl alcohol in the polyvinyl alcohol-tannic acid mixed solution is 20-30 mg / mL, and the concentration of tannic acid is 20-30 mg / mL.
8. The method for preparing a Janus photothermal distillation membrane for ship oily wastewater according to claim 7, characterized in that: The polyvinyl alcohol-tannic acid mixed solution is heated in a water bath before spraying, the water bath heating temperature is 80-100° C., and the water bath heating time is 5-7 hours; the spraying volume of the polyvinyl alcohol-tannic acid mixed solution is 1-2 mL.
9. The Janus photothermal distillation membrane for ship oily wastewater prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of modified ultrafiltration membrane co-coated by utilizing dopamine and functional CNTs (Carbon Nanotubes)
CN108854603A
High-flux super-hydrophilic / underwater super-oleophobic Janus membrane modification method
CN113144903A
Preparation method of hydrogel Janus membrane with wetting resistance, pollution resistance and scaling resistance
CN116020280A
Preparation method of anti-pollution and wetting-resistant composite distillation membrane
CN116036887A
Novel Janus composite hollow fiber membrane for membrane distillation and preparation method thereof
CN118988001A